LIBERALISME PENDIDIKAN (Analisis Pemikiran Carl R. Rogers dan Implementasinya Dalam Pendidikan Agama Islam) (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
To embody the spirit of liberalism, Rogers has been lowered into a more practical method of learning, while Islam does not have the concept of ( practical method) education that truly reflects liberal education. However, the differences and advantages of one another, not hinder to combine these two concepts . Because if the two concepts are combined, then education will produce high-quality output : master common knowledge (non - religious) and religious knowledge, capable of autonomous thinking, creative, wise and able to resolve any problems faced . Merging these two concepts should not be exhaustive, but merely complementary. Islamic education is already mempuyai spirit of liberalism, the philosophy and objectives clear, no need to adopt the goals and spirit of liberalism offered Rogers. In contrast, the Islamic education system must adopt a way of teaching (practical method) of educational liberalism Rogers.